2016
DOI: 10.1016/j.chroma.2016.11.047
|View full text |Cite
|
Sign up to set email alerts
|

Separation of 44Ti from proton irradiated scandium by using solid-phase extraction chromatography and design of 44Ti/44Sc generator system

Abstract: Scandium-44g (half-life 3.97h [1]) shows promise for positron emission tomography (PET) imaging of longer biological processes than that of the current gold standard, F, due to its favorable decay parameters. One source ofSc is the long-lived parent nuclide Ti (half-life 60.0 a). ATi/Sc generator would have the ability to provide radionuclidically pure Sc on a daily basis. The production ofTi via the Sc(p,2n) reaction requires high proton beam currents and long irradiation times. Recovery and purification of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 23 publications
2
33
0
Order By: Relevance
“…Although it was proposed a long time ago [20], hitherto only a 185 MBq generator has been reported [21] and some post-elution purification of 44g Sc has been described [22]. In recent years, more effort has been devoted to the separation of the parent 44 Ti via anion-exchange chromatography [23] and the daughter 44g Sc through cation-exchange chromatography [24]. The generator activity, however, has still been limited to about 175 MBq.…”
Section: Production Of 44g Scmentioning
confidence: 99%
“…Although it was proposed a long time ago [20], hitherto only a 185 MBq generator has been reported [21] and some post-elution purification of 44g Sc has been described [22]. In recent years, more effort has been devoted to the separation of the parent 44 Ti via anion-exchange chromatography [23] and the daughter 44g Sc through cation-exchange chromatography [24]. The generator activity, however, has still been limited to about 175 MBq.…”
Section: Production Of 44g Scmentioning
confidence: 99%
“…43 Sc can be produced via proton irradiation of 43 Ca or 46 Ti, as well as a-irradiation of 40 Ca or deuteron irradiation of 44 Ca (5-7). 44g,m Sc can be produced via proton irradiation of 44 Ca, 47 Ti, or 45 Sc or deuteron irradiation of 44 Ca (2,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Enriched targets are preferred to avoid production of contaminants such as 46,48 Sc (18).…”
mentioning
confidence: 99%
“…Researchers have also studied the 46 Ti(p,a) 43 Sc reaction and showed that this pathway produced 43 Sc of higher radionuclidic purity than when using the 43 Ca(p,n) 43 Sc production route; however, the latter route produced 43 Sc in higher yields (18). Another source for 44g Sc is the 44 Ti/ 44 Sc generator (8,23). Although the generator method has been investigated, only a small number of facilities in the world have these generators in use.…”
mentioning
confidence: 99%
“…Scandium-44 (β + = 94%, E ~ β = 0.632 MeV) has a physical half-life of 3.97 h and can be produced on two different ways, via 44 Ti/ 44 Sc-generator or cyclotron [30][31][32][33][34][35][36]. Another potential advantage of scandium(III) in nuclear medicine is its radioisotope scandium-47 (β − , primary �-ray of 159 keV and t½ = 3.3 d) which is suitable for therapeutical application.…”
Section: Part I: Radiochemistrymentioning
confidence: 99%